(untitled) (Applied Biological Research, 2019)
Indian mustard (Brassica juncea L.) which occupies largest area among the all oleiferous Brassicas, is an important source of nutritionally important fatty acid and micronutrients for animal including humans. The present study was aimed to evaluate the fatty acid and mineral composition of 30 agro morphologically distinct quality germplasm of Indian mustard. The quality germplasms were evaluated for fatty acid profiling by injecting methyl ester sample into SP-2300 (2%) + SP-2310 (3%) packed silica column. Micro nutrients were determined by atomic absorption spectrophotometric method. Fatty acid variability in quality germplasm revealed the erucic acid content of <2% in genotypes BC3-BC4-1 (0.57%), F3-F4-1 (0.67%), F3-F4-3 (1.05%), NUDH-YJ-3-3 (0.28%), F3-F4-2 (0.74%), F4-F5-1 (0.72%), PRQ 2004-8 (0.51%) and PRQ-2005-1 (1.24%). ω6/3 ratio was fairly better in genotypes PLGM-2002-2-7(2.28), LG BC 2005-6-8 (2.20), PRQ 2004-9 (1.92), PRQ-2005- 11-BE (1.91) and F4-F5-5 (2.13). The mineral proportion of meals showed that all quality genotypes had variable amounts of N, P, K, S, Ca, Mg, Fe, Mn, Zn and Cu. The identified genotypes having low erucic acid, optimal ratio of essential fatty acids and promising micronutrients can be used for preparation of functional food or for determining the quality traits and nutritional status of Indian mustard.